2020
DOI: 10.3390/nu12030716
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Low Fermentable Oligosaccharide, Disaccharide, Monosaccharide, and Polyol Diet and Its Effects on Quality of Life in an Italian Cohort

Abstract: The low Fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP) diet has demonstrated excellent results in terms of symptom control and health-related quality of life (HRQoL) in irritable bowel syndrome (IBS) sufferers, but patients have complained about unsatisfying taste, difficulty in following the diet, and time consumption. To investigate the feasibility of the low FODMAP diet in an Italian (Sardinian) cohort, sixty consecutive eligible outpatients (11 men and 49 women) with IBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Three studies on stool habit change in patients with IBS-D showed a significant decrease in stool frequency (MD, −5.56/week; 95% CI, −7.40, −3.72) and a significant improvement in stool consistency (MD, −0.86; 95% CI, −1.52, −0.19) in the LFD group compared to that in the control group. This study result is consistent with those of previous studies that showed LFD is particularly effective at improving stool habits in IBS-D type patients [ 42 , 43 ]. This can be explained by the fact that food-related symptoms are most often reported by patients with IBS-D, and LFD induces a reduction in osmotic action exerted by FODMAPs in the intestinal lumen and reduces diarrhea [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Three studies on stool habit change in patients with IBS-D showed a significant decrease in stool frequency (MD, −5.56/week; 95% CI, −7.40, −3.72) and a significant improvement in stool consistency (MD, −0.86; 95% CI, −1.52, −0.19) in the LFD group compared to that in the control group. This study result is consistent with those of previous studies that showed LFD is particularly effective at improving stool habits in IBS-D type patients [ 42 , 43 ]. This can be explained by the fact that food-related symptoms are most often reported by patients with IBS-D, and LFD induces a reduction in osmotic action exerted by FODMAPs in the intestinal lumen and reduces diarrhea [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this respect, considerable efforts have been made in recent years to determine the FODMAP content of foods and to establish cut-off values for their classification in low-and high-content food [17]. Nevertheless, there is still a lack of information about composition of food products in different regions and so it is difficult to establish an accurate FODMAP intake worldwide [29]. Moreover, some FODMAPs, such as fructans, are more difficult to find in food composition databases, and their intake is not always determined in diet-related studies [6,22,24,25,30].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the results shown in the present research are limited to the Spanish population. Several authors have proposed data related to different countries or cultures for food composition databases and intake [29,40]. Hence, we would like to highlight the importance of this approach performed to calculate the total FODMAP intake, in order to make its use widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when considering only IBS-D patients, our positive data aligned with those in the literature. The reduction of the osmotic action in the intestinal lumen due to FODMAPs and the correction of the “minimal inflammation” in these patients have both been considered possible determinants of the positive effects of LFD [ 43 ].…”
Section: Discussionmentioning
confidence: 99%